Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0134
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids

Abstract: The sections in this article areIntroductionFlavonoids as PigmentsFlavonoid BiosynthesisRegulation of Flavonoid Biosynthesis in FlowersGenetic Modification of Flower ColourConcluding CommentsAcknowledgements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 254 publications
0
34
0
Order By: Relevance
“…Their activity depends on several factors, such as the sulfation degree, the molecular weight, and the sulfation positions. Additionally, anthocyanins are one of the major groups of hydrosoluble pigments belonging to the flavonoid class (Schwinn & Davies 2004). These compounds have an anti-inflammatory and an anticarcinogenic action to prevent cardiovascular diseases, to reduce the action of diabetes and to exhibit antioxidant capacity (He & Giusti 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Their activity depends on several factors, such as the sulfation degree, the molecular weight, and the sulfation positions. Additionally, anthocyanins are one of the major groups of hydrosoluble pigments belonging to the flavonoid class (Schwinn & Davies 2004). These compounds have an anti-inflammatory and an anticarcinogenic action to prevent cardiovascular diseases, to reduce the action of diabetes and to exhibit antioxidant capacity (He & Giusti 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin are the major water-soluble pigments, produced by the flavonoid biosynthesis pathway, widely distributed in flowering plants and responsible for pink, purple, red, and blue of many flowers and fruits (Chandler & Tanaka, 2007; Wessinger & Rausher, 2014). Currently, all structural genes involved in the anthocyanin synthesis have been well characterized in many species (Schwinn & Davies, 2004; Grotewold, 2006; Guo et al, 2014). Anthocyanins are synthesized in the cytosol, and are not stabilized until they are transported into vacuole (Kitamura, Shikazono & Tanaka, 2004; Gomez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that flavonoid absorption at 350 nm is responsible for yellowing (Schwinn and Davies, 2004). However, whether leaf yellowing caused by O 3 is related to flavonoid accumulation has previously been unclear.…”
Section: Elevated O 3 Levels Accelerate Leaf Yellowing In Flowering Pmentioning
confidence: 99%
“…Flavonoids, which exist in almost all plant tissues, protect the plants from stress damage owing to their antioxidant ability (Davies, 2004;Huang et al, 2013). These widely known pigments absorb light at λ 350nm , contributing to leaf yellowing (Schwinn and Davies, 2004). However, little research has focused on investigating whether leaf yellowing is linked to flavonoid biosynthesis when the plant is exposed to O 3 .…”
Section: Introductionmentioning
confidence: 99%